1988
DOI: 10.1111/j.1600-0536.1988.tb02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized eruption with severe liver dysfunction associated with occupational exposure to trichloroethylene

Abstract: Generalized dermatitis due to trichloroethylene is rare. A 21-year-old printer developed exfoliative dermatitis with mucous membrane involvement, fever and liver dysfunction after a 2-week occupational exposure to trichloroethylene. Positive patch-test reactions to trichloroethylene and to one of its metabolites, trichloroethanol, were observed. This dermatitis is considered to be mediated by a delayed-type hypersensitivity mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…He continued going to work, but died fourteen days later. Nakayama et al 7) reported a patient intoxicated by the use of trichloroethylene as a degreasing agent. Two wk after commencing work, systemic erythema and liver dysfunction with high fever were observed in this patient.…”
Section: Clinical Manifestation Of Trichloroethylene-related Generalimentioning
confidence: 99%
See 1 more Smart Citation
“…He continued going to work, but died fourteen days later. Nakayama et al 7) reported a patient intoxicated by the use of trichloroethylene as a degreasing agent. Two wk after commencing work, systemic erythema and liver dysfunction with high fever were observed in this patient.…”
Section: Clinical Manifestation Of Trichloroethylene-related Generalimentioning
confidence: 99%
“…Together with anesthetic action, hepatic damage, polyneuropathy, trigeminal neuropathy, and dermatitis with skin irritation are familiar diseases which occur as a result of exposure 1,2) . In addition to the non-specific skin irritation resulting by the defatting action, severer generalized dermatitis with hepatitis, which includes Stevens-Johnson syndrome and toxic epidermal necrolysis, sometimes occurs after exposure to trichloroethylene [3][4][5][6][7][8][9][10] . Such dermatitis is generally known to occur subsequent to the administration of various medicines and infections-i.e., antibiotics such as sulfonamides, anticonvulsives such as carbamazepine and phenobarbital, anti-inflammatory medications such as acetylsalicylic acid and paracetamol, anti-parasitic medications such as albendazole and tinidazole, viruses, mycoplasma, and other bacterial infections [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…The disorders are not caused solely by drugs. A close link between occupational solvent exposure, mostly trichloroethylene (TCE), and severe generalized skin disorders has been suggested by a series of case reports [3][4][5][6][7][8][9][10][11] . Recently, the number of patients suffering from TCE-related severe skin disorders has been increasing in Asia, especially the Philippines, Singapore, Taiwan and Guangdong Province, China 10,12,13) .…”
mentioning
confidence: 99%
“…7,18 Not all patients showed a positive reaction for TCE on patch testing. In fact, we found that patch testing was negative for TCE itself, but positive for trichloroethanol, trichloroacetic acid and chloral hydrate in our patient.…”
Section: Results Of Patch Testingmentioning
confidence: 99%